2014
DOI: 10.1063/1.4905283
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of uniformly dispersed nanoparticle-doped chalcogenide glass

Abstract: The dispersion of metallic nanoparticles within a chalcogenide glass matrix has the potential for many important applications in active and passive optical materials. However, the challenge of particle agglomeration, which can occur during traditional thin film processing, leads to materials with poor performance. Here, we report on the preparation of a uniformly dispersed Ag-nanoparticle (Ag NP)/chalcogenide glass heterogeneous material prepared through a combined laser- and solution-based process. Laser abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…1,2 The agglomeration of filler particles interrupts the effective penetration and crystallization of the polymer segment in the unoccupied regions, 3,4 as well as the consequent effect of confining the nanoparticles. 5 As insufficient penetration of polymer brushes in the interphase zone naturally results in the formation of a vacancy zone in the agglomeration, it is generally believed to degrade the overall mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The agglomeration of filler particles interrupts the effective penetration and crystallization of the polymer segment in the unoccupied regions, 3,4 as well as the consequent effect of confining the nanoparticles. 5 As insufficient penetration of polymer brushes in the interphase zone naturally results in the formation of a vacancy zone in the agglomeration, it is generally believed to degrade the overall mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism has been explained through the initial formation of Ag−S bond at the silver and ChG interface, followed by the generation of electron-hole pairs and by the mobility of holes toward the silver layer, while Ag + move in the opposite direction [19]. Recently, we showed the formation of metallic silver nanoparticles in chalcogenide solution using laser ablation of a silver target [21]. Although studies on Ag photodoping in As 2 S 3 have achieved considerable advances, the synthesis of silver sulfide nanocrystals in such material has not been demonstrated yet.…”
Section: Introductionmentioning
confidence: 99%
“…12 The glasses dissolve in organic solvents and can then be doped, spin coated, or even inkjet printed with relative ease. [12][13][14][15] Previous research has shown numerous successful applications, including molded mid-IR waveguides, drop-cast photonic crystals, and optical bers with a nonlinearity-enhancing ChG coating. [16][17][18][19] The pioneering work on ChG solutions was done by Chern et al using As 2 S 3 in n-propylamine and n-butylamine as test systems.…”
Section: Introductionmentioning
confidence: 99%